Multi-omics reveal the effects and regulatory mechanism of dietary echinocystic acid supplementation on abdominal fat and liver steatosis in broiler chickens - Lianggui Xiao; Jiazhe Liu; Liangshan Qin; Shan Deng; Guodong Mo; Dandan Zhang; Ben Huang (Poultry Science)
The accumulation of abdominal fat and the metabolic dysfunction-associated fatty liver disease (MAFLD) are prevalent problems in the poultry industry, and seriously compromise broiler health and reduce economic benefits. Echinocystic acid (EA), a natural product with anti-inflammatory and antioxidant effects, has been demonstrated to reduce abdominal fat deposition and improve intestinal inflammation in mice. However, it has not been reported in poultry research.In this study, we employed chicken hepatocytes (Leghorn male hepatoma cells, LMHs) to construct an oleic acid and palmitic acid (OA/PA)-induced MAFLD model in vitro and 60 male K90 chickens were induced MAFLD by a high-fat diet (HFD) to examine the impact of EA on liver-lipid metabolism and abdominal fat deposition. Moreover, metabolomic analysis, 16S rDNA gene sequencing, and transcriptomic profiling were performed to determine the mechanism of EA.The results showed that EA (10 μM) significantly reduced triglyceride (TG) and total cholesterol (TC) levels in vitro. Moreover, EA reduced abdominal fat deposition without affecting growth performance. EA significantly decreased TC, TG, and low-density lipoprotein-cholesterol (LDL-C) levels, and increased high-density lipoprotein-cholesterol (HDL-C) levels in the blood. Additionally, EA supplementation altered the composition of the intestinal microbiota, particularly by decreasing the ratio of Firmicutes to Bacteroidetes. Furthermore, liver metabolomics analysis revealed that EA increased the abundance of metabolites related to arginine metabolism and mitochondrial oxidation pathways, and these metabolites were predicted to be positively correlated with the gut genera enriched by EA. EA also altered the expression patterns of genes related to liver lipid metabolism and inflammation, particularly CYP7A1, CYP7B1, CYP3A5, and ACAT, which are enriched in the PPAR signaling pathway and steroid hormone metabolism. Moreover, correlation analysis revealed that there was a close correlation between differential gut microbiota, metabolites, and gene expression profiles.Collectively, the results indicated that EA may alleviate MAFLD by regulating steroid hormone metabolism and modulating the gut microbiota. EA may be a candidate feed additive to prevent abdominal fat deposition and MAFLD in the broiler industry.